Guidance and Counseling Teachers’ Role in Students’ Emotional Maturity at MAN 1 Medan - Elsi Sumita Harahap; Abdurrahman Abdurrahman (Jurnal IPTEK Bagi Masyarakat, 2026)
This study aims to analyze the role of the guidance and counseling teacher in supporting the development of emotional maturity among Grade XI students at MAN 1 Medan. This research employed a descriptive qualitative approach involving one guidance and counseling teacher as the main informant and two Grade XI students as supporting informants selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. Data trustworthiness was strengthened through source and technique triangulation. The findings indicate that some students’ emotional maturity was still developing, as reflected in irritability, difficulty controlling anger, anxiety when facing academic pressure, and strong influence from peers and family conditions. The guidance and counseling teacher supported students through classroom guidance, information services, group guidance, individual counseling, and an empathetic personal approach. These services helped students recognize their emotions, calm themselves, consider their responses before acting, and become more open in expressing personal problems. The findings suggest that guidance and counseling services can serve as a practical school-based support strategy for gradually and contextually developing students’ emotional maturity.